High frequency trading and market quality : an analysis on Dow Jones industrial average and its component stocks - Yap, Jia Wei (2013)
This paper examines the market quality in the US securities market surrounding the “Flash Crash” on May 6, 2010 by focusing on the Dow Jones Industrial Average (DJIA) and its component stocks. The study defines market quality in three dimensions: stock price’s volatility, trading activity, and liquidity. The data collected is analyzed at the per-second level during the regular trading hours across the stock exchanges. Test results show that the market was efficient after the “Flash Crash”, and that High Frequency Trading (HFT) facilitates price discovery. Trading volume, number of trades, and stock price’s volatility increased during the event, but subsequently decreased back to normal over the post 5-day period. Likewise, May 6 recorded the largest decrease in liquidity and trade size, but it gradually returned to normal. A more detailed analysis indicates a lead-lag relationship between the 30 component stocks and the DJIA Exchange Traded Fund (ETF). Together with the autocorrelation analysis conducted, the study concludes that the securities market is efficient in processing new information.